DAKWAH ISLAM H. ISMAIL MUNDU DI KALIMANTAN BARAT TAHUN 1907-195 - Karel Juniardi (Candrasangkala: Jurnal Pendidikan dan Sejarah, 2016)
Abstrak: This study aimed to describe (1) Brief History of the Kingdom of Kubu; (2) The Islamic Propagation Ismail Mundu; (3) Heritage Ismail Mundu in preaching. This study uses historical research stages heuristic, criticism, interpretation and historiography. This research was conducted in the district of Kubu Raya Teluk Pakedai West Kalimantan Province. The data source consists of informants, literature and documents. Data collection techniques using the technique of direct communication, literature, and documentation study. While the data collection tool used is interview, literature analysis and document analysis. The study concluded that: (1) the Kingdom of Kubu is one of the Islamic empire founded by traders from Hadramawt. Kubu kingdom ruled by the descendants of Al Idrus and recognized by the Netherlands as one of the unoccupied areas in West Kalimantan; (2) Haji Ismail Mundu are scholars Bugis descent who was born in West Kalimantan. He had studied Islam in Mecca. Later, he taugth the religion of Islam in West Kalimantan, especially in the area of Kubu so that he gets the sympathy of King Kubu and was appointed as the Mufti of the Kingdom of Kubu; (3) Haji Ismail Mundu died in 1957 by bequeathing some of his teachings, such as the book collection of wird, the Minutes of Practice, Book Mukhtasar Aqaid and Hukmin Book of Nikah. Apart form the books and manuscripts, relics of Haji Ismail Mundu another form of a mosque called Masjid batu located in the Gulf Pakedai Kubu Raya. The Mosque was built by Haji Ismail Mundu as a center of Islamic learning for him and his disciples.